Sneak Peek as Micronarrative Trailers in Love Themed and Ramadan Indonesian Soap Operas (Sinetron) - Setiawan, Danang; Mustikaningsih, Mega; Aisyah, Rahmawati; Hanifah, Alia Nur; Khotimah, Kusnul; Fadila, Suci Thiram (Titian: Jurnal Ilmu Humaniora, 2024)
This study delves into the phenomenon of narrative coherence within the context of sneak peeks in Indonesian soap operas with themes centered  around love and Ramadan. Addressing gaps in previous research concerning the presentation of sneak peeks as either trailers or micronarratives in Indonesian soap operas, this research specifically focuses on how love-themed and Ramadan-themed soap operas present sneak peeks as trailers or micronarratives. The study employs a theoretical articulated by Venditti et al. (2017) to address the research questions. The findings of the research reveal that sneak peeks in love-themed soap operas tend to lean towards a trailer format, whereas approach, utilizing the concept of trailers proposed by Kernan (2004) and micronarratives as those in Ramadan-themed soap operas tend to adopt a more narrative-oriented structure. This study illustrates variations in the presentation of sneak peeks within Indonesian soap operas, with love-themed soap operas emphasizing the trailer aspect, while Ramadan-themed soap operas prioritize the narrative element. Abstrak Penelitian ini mengulas fenomena naratif yang kohesif dalam konteks sneak peek sinetron Indonesia bertema cinta dan Ramadan. Menyelidiki kesenjangan dalam penelitian sebelumnya terkait penyajian sneak peek sebagai trailer micronarrative dalam sinetron Indonesia, penelitian ini fokus pada cara sinetron bertema cinta dan bertema Ramadan menyajikan sneak peek sebagai trailer micronarrative. Kami menggunakan pendekatan teoritis dengan memanfaatkan konsep trailer oleh Kernan (2004) dan micronarrative oleh Venditti dan rekan-rekannya (2017) untuk menjawab permasalahan. Hasil penelitian menunjukkan bahwa sneak peek dalam sinetron bertema cinta cenderung bersifat trailer, sementara sneak peek dalam sinetron bertema Ramadan cenderung bersifat naratif. Penelitian ini menggambarkan variasi dalam presentasi sneak peek dalam sinetron Indonesia, di mana sinetron bertema cinta lebih menekankan aspek trailer, sedangkan sinetron bertema Ramadan lebih fokus pada aspek naratif.